2003
DOI: 10.1016/s0029-7844(03)00529-5
|View full text |Cite
|
Sign up to set email alerts
|

Total versus subtotal hysterectomy: a survey of gynecologists

Abstract: Most gynecologists surveyed favor total abdominal hysterectomy over subtotal hysterectomy. Few counsel women regarding the options of total and subtotal hysterectomy or offer a choice between the procedures. Given that there are no convincing data proving the superiority of either procedure over the other, it may be reasonable to discuss the potential advantages and disadvantages of both procedures with women undergoing hysterectomy for benign disease and to offer them a choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
1
12
1
4
Order By: Relevance
“…A recent survey conducted in the MidAtlantic states revealed that despite believing that the risk of future cancer of the cervical stump was minimal, the majority of respondent gynecologists indicated that prevention of cervical cancer and doing away with the need for pap smears were the key reasons for recommending a total AH. 36 Removal of the cervix as a preventative measure is not borne out by present evidence as the risk of cervical cancer after supracervical hysterectomy has been reported to be less than 0.1%. Moreover, conversion from a normal to a high grade smear after 3 consecutive normal smears is as low as 22 per 10,000 in women aged 30 to 49 and seems to remain stable thereafter.…”
Section: The Current Role Of Supracervical Hysterectomymentioning
confidence: 79%
“…A recent survey conducted in the MidAtlantic states revealed that despite believing that the risk of future cancer of the cervical stump was minimal, the majority of respondent gynecologists indicated that prevention of cervical cancer and doing away with the need for pap smears were the key reasons for recommending a total AH. 36 Removal of the cervix as a preventative measure is not borne out by present evidence as the risk of cervical cancer after supracervical hysterectomy has been reported to be less than 0.1%. Moreover, conversion from a normal to a high grade smear after 3 consecutive normal smears is as low as 22 per 10,000 in women aged 30 to 49 and seems to remain stable thereafter.…”
Section: The Current Role Of Supracervical Hysterectomymentioning
confidence: 79%
“…Despite this, when US gynecologists are surveyed, TAH is still performed over SCH. The most common reason for this is fears related to future risk for developing cervical cancer [ 6 ], even though there is no evidence to support this concern.…”
Section: Defi Nitions Of Hysterectomymentioning
confidence: 99%
“…However, in over 95 % of the pathological conditions for which hysterectomy is indicated, the removal of the uterine cervix is not necessarily required [8,9]. In clinical practice, however, less than 20 % of gynecologists offer patients the possibility to choose between TLH and LSH [10]. Despite various data available in literature regarding the short-and long-term surgical risks and rewards pertaining to the procedure when hysterectomy is indicated, debate continues as to which approach is to be considered the most appropriate.…”
Section: Introductionmentioning
confidence: 99%